Role of Health Insurance in Child Health Care Utilization in Misungwi District, Tanzania (Tanzania Medical Journal, 2021)
In the original version of this article, the consent for publication section was incorrectly written. The section is correctly written below.Consent for publicationThis manuscript is an original work written by the authors, SY, GM and DC who are aware of its content and approve its submission. It is also important to mention that the manuscript has not been published elsewhere in part or in entirety and is not under consideration by another journal. All authors give their consent for publication in the Tanzania Medical Journal. ReferenceSimon Yasin, Gladys R. Mahiti, Dereck Chitama, Role of Health Insurance in Child Health Care Utilization in Misungwi District, Tanzania; TMJ Vol 32 No. 3 (2021); 18-35